Construction of a spectrally stable self-similar blowup solution to the supercritical corotational harmonic map heat flow. (27th June 2018) - Biernat, Pawel; Donninger, Roland
Abstract: We prove the existence of a (spectrally) stable self-similar blow-up solution f 0 to the heat flow for corotational harmonic maps from to the three-sphere. In particular, our result verifies the spectral gap conjecture stated by one of the authors and lays the groundwork for the proof of the nonlinear stability of f 0 . At the heart of our analysis lies a new existence result of a monotone self-similar solution f 0 . Although solutions of this kind have already been constructed before, our approach reveals substantial quantitative properties of f 0, leading to the stability result. A key ingredient is the use of interval arithmetic: a rigorous computer-assisted method for estimating functions. It is easy to verify our results by robust numerics but the purpose of the present paper is to provide mathematically rigorous proofs .